Design and optimization of powertrain system for prototype fuel cell electric vehicle - S.M.H.S. Omar; N.M. Arshad; I.M. Yassin; M.H.A.M. Fakharuzi; T.A. Ward (Journal of Mechanical Engineering and Sciences, 2015)
This paper reports the analysis of an automatic intelligent controller for driving a prototype fuel cell electric vehicle over different obstacles while maintaining all systems at maximum efficiency during completion of a race within a specified time. The objective is to reduce driving errors, such as excessive driving, or over revving the throttle while controlling the energy usage at the minimum point and improving driving skills for the Shell Eco-marathon Asia 2014 race. The vehicle is equipped with a proton exchange membrane (PEM) fuel cell system, a brush DC motor and a DC/DC converter. This prototype vehicle is a single-seater type of car and has a streamlined body shape that is designed for energy-efficiency racing where the objective is to achieve the furthest distance with the least amount of fuel in a specified time. In the design process, the car’s fuel-cell efficiency, energy demand, track behavior, motor efficiency analysis, and driving control strategy need to be monitored and used to verify the designed automated intelligent controller. Experiments on the automated intelligent controller were undertaken to analyze the performance of the powertrain system for a certain given time. This powertrain system for automated intelligent controller analysis is part of the energy efficiency study of the electric vehicle. It forms the knowledge base for the next detailed energy efficiency analysis.